Situation Report: Romania, 22 September 1977 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Sweeping Criticisms by Ceausescu at Bucharest Meeting Pensions Bill Amended - without Assembly Approval Valter Roman Traces Historical Roots of Euro-Communism Intensification of Relations with China Negotiations on Fuel and Energy: Credit for Romanian Economy